Sociological perspectives on the economic geography of projects: The case of project-based working in the creative industries - Allan Watson (2012)
In recent years, there has been a growing concern in economic geography with the organisational practices of project-based working, involving a multiplicity of organisational and personal social networks. Paralleling this debate has been a growing academic interest in the cultural economy and the conditions of creative work, itself characterized by project-based working. Cultural and creative workers are argued to symbolise contemporary transformations of work more than any other group of workers. However, despite this being a wide trans-disciplinary area of enquiry, little economic geography literature has engaged explicitly with perspectives being developed in other disciplines, in particular sociology and cultural and media studies, on the experience and conditions of work in project-based industries. In this paper I argue for the incorporation of sociological perspectives into our analyses of projects, in order to address the lack of attention to the sociological, political and cultural issues of work. Such an approach, I suggest, can contribute to the economic geography of projects in three ways; first it moves beyond structural analyses to allow for an understanding of the importance of agency in project work; second it allows us to move on from firm-level analyses to develop an understanding of the complex social networks involved in project-based working; and finally it moves on from research at the meso-level on inter- and intra-firm networks to provide micro-level analyses of project work.